NGOization, politicization and polarization of Roma civil society in Turkey - Sayan, Pınar; Duygulu, Şirin (Routledge Journals, Taylor & Francis Ltd, 2022)
Roma are one of the most marginalized and discriminated-against groups in Turkey. During the last decade, however, a new trend has emerged: the institutionalization of Roma civil society. Roma civil society has moved from having no registered organizations in 2004 to having 336 non-governmental organizations (NGOs) as of 2020. This paper critically analyses the rapid expansion of Roma NGOs in Turkey and discusses the impact of this expansion on Roma communities. Based on a systematic analysis of 14 semi-structured interviews conducted with those who have experience within Roma NGOs, this article argues that the potential positive effects of the expansion of institutionalized Roma civil society have been hampered by limited resources, blurred state-civil society relations, as well as polarization in Turkish society. As a result, Roma civil society became politicized and polarized. While providing insights into an understudied segment of civil society in Turkey, this study also provides further evidence for criticisms about the current state of Turkish civil society.
Keywords: Civil Society; NGOization; Polarization; Roma; Turkey